2012
DOI: 10.1002/j.2334-5837.2012.tb01431.x
|View full text |Cite
|
Sign up to set email alerts
|

11.5.1 Early Formulation Model‐Centric Engineering on NASA's Europa Mission Concept Study

Abstract: By leveraging the existing Model‐Based Systems Engineering (MBSE) infrastructure at JPL and adding a modest investment, the Europa Mission Concept Study made striking advances in mission concept capture and analysis. This effort has reaffirmed the importance of architecting and successfully harnessed the synergistic relationship of system modeling to mission architecting. It clearly demonstrated that MBSE can provide greater agility than traditional systems engineering methods. This paper will describe the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 2 publications
0
45
0
1
Order By: Relevance
“…• Concept exploration -developing mission architectures using an MBSE approach enabled some organizations to explore a much broader set of design options in the same amount of time and resources as conventional methods. [10] • Design reuse -organizations have found that MBSE models can be reused across product lines to achieve significant savings in upfront design effort. [11] • System margins analyses -detailed representation of the system in the MBSE model enables improved systems-level characterizations such as weight, budget, and power requirements analyses.…”
Section: Key Findings From Case Studies Without Metricsmentioning
confidence: 99%
“…• Concept exploration -developing mission architectures using an MBSE approach enabled some organizations to explore a much broader set of design options in the same amount of time and resources as conventional methods. [10] • Design reuse -organizations have found that MBSE models can be reused across product lines to achieve significant savings in upfront design effort. [11] • System margins analyses -detailed representation of the system in the MBSE model enables improved systems-level characterizations such as weight, budget, and power requirements analyses.…”
Section: Key Findings From Case Studies Without Metricsmentioning
confidence: 99%
“…Among other topics mentioned previously, NASA/JPL has developed an Architecture Framework Tool (AFT) for Architecture Description [9], which provides an overarching perspective on one of the views needed for our Task 3 vision model, and is partially supported with their evolving Open-MBEE [43].…”
Section: Single Source Of Truth Modeling Patterns Ontologies Profimentioning
confidence: 99%
“…They are modeling their artifacts and activities to generate the controls for a workflow engine. Figure 27 provides an overarching perspective on one of the views extracted from a report [9] that is applicable to the Vision model:  Blocks in the diagram define categories of items requiring exposition in the architecture description o Accompanying each category is a template (not shown) specifying the sorts of information required for each member of that category  Stakeholders and their Concerns are the drivers for everything else in the architecture, i.e., they can be considered the 'entrance points' to explore the framework o This is somewhat analogous to the purpose of the Study Views developed at NAVAIR, although NAVAIR does not have a similar representation of its context in a model representation  The Element is a place holder for aspects of the System to be designed (i.e., Program of Interest in Figure 25)  The Models, the Analyses performed on them, and the Scenarios, which relate to the "Containing System" (e.g., for a Program of Record) complete the blocks of the Architecture Description This concept, with the information provided on the reference architecture and the associated modeling patterns provides one of the best stories we have heard as it relates to formalizing the concept of the Vision model. This perspective informed our development of a NAVAIR-oriented concept reflected in Figure 25.…”
Section: Reference Architecture and Model Based Engineering Environmentmentioning
confidence: 99%
“…As described before, one of the benefits of the MBSE approach is that we are able to generate a consistent set of systems engineering products from a single-source-of-truth, which we capture as models specified in SysML. [3] Block Definition Diagrams (BDD) for example are created as well as Internal Block Diagrams (IBD) to describe the internal components of a system and their interconnections (connectors in SysML). An example [4] of an IBD created in the Europa Mission study is shown in Fig.…”
Section: Deployment Viewsmentioning
confidence: 99%